Erythrocyte Alloimmunity and Genetic Variance: Results from the Collaborative Study of Alloimmunity to Antigen Diversity in Asian Populations (All ADP). (October 2020) - Takeshita, Akihiro; Watanabe, Hiroko; Yamada, Chiaki; Nadarajan, Veera Sekaran; Permpikul, Parichart; Sinkitjasub, Attapong; Natalie, Chan Pui Ha; Zhao, Shuming; Han, Kyou Sup; Kim, Dae Won; Suh, Jang Soo; Kim, Hyun Ok; et al.
Abstract: As an East-Asian international study, we evaluated erythrocyte alloimmunity by gender and history of transfusion or pregnancy. In total, data from more than 1, 826, 000 patients were analyzed, from whom 26, 170 irregular erythrocyte antibodies were detected in 22, 653 cases. Antibody frequencies in these cases were as follows: anti-E, 26.8%; anti-Le a, 20.0%; anti-P1, 7.1%; anti-M, 6.4%; anti-Mi a, 5.6%; anti-c + E, 5.6%; anti-Le b, 4.6%; anti-D, 2.8%; anti-Fy b, 2.6%; anti-Le a +Le b, 2.5%; anti-Di a, 2.0%; and others. For pregnant patients, anti-D (12.7%) was statistically more frequent. For transfused patients, anti-E (37.3%), anti-c + E (9.5%), anti-C + e (3.3%) and anti-Jk a (3.1%) were significantly more frequent.